TANK-Binding Kinase 1 (TBK1) Isoforms Negatively Regulate Type I Interferon Induction by Inhibiting TBK1-IRF3 Interaction and IRF3 Phosphorylation - Hu, Yi Wei; Zhang, Jie; Wu, Xiao Man; Cao, Lu; Nie, Pin; Chang, Ming Xian (Frontiers in Immunology, 2018)
TANK-binding kinase 1 (TBK1) is an important serine/threonine-protein kinase that mediates phosphorylation and nuclear translocation of IRF3, which contributes to induction of type I interferons (IFNs) in the innate antiviral response. In mammals, TBK1 spliced isoform negatively regulates virus-triggered IFN-β signaling pathway by disrupting the interaction between RIG-I and MAVS. However, it is still unclear whether alternative splicing patterns and the function of TBK1 isoform(s) exist in teleost fish. In this study, we identify two alternatively spliced isoforms of TBK1 from zebrafish, termed TBK1_tv1 and TBK1_tv2. Both TBK1_tv1 and TBK1_tv2 contain an incomplete STKc_TBK1 domain. Moreover, the UBL_TBK1_like domain is also missing for TBK1_tv2. TBK1_tv1 and TBK1_tv2 are expressed in zebrafish larvae. Overexpression of TBK1_tv1 and TBK1_tv2 inhibits RIG-I-, MAVS-, TBK1- and IRF3-mediated activation of IFN promoters in response to SVCV infection. Also, TBK1_tv1 and TBK1_tv2 inhibit expression of IFNs and IFN-stimulated genes (ISGs) induced by MAVS and TBK1. Mechanistically, TBK1_tv1 and TBK1_tv2 competitively associate with TBK1 and IRF3 to disrupt the formation of a functional TBK1-IRF3 complex, impeding the phosphorylation of IRF3 mediated by TBK1. Collectively, these results demonstrate that TBK1 spliced isoforms are dominant negative regulators in RIG-I/MAVS/TBK1/IRF3 antiviral pathway by targeting the functional TBK1-IRF3 complex formation. Identification and functional characterization of piscine TBK1 spliced isoforms may contribute to understanding the role of TBK1 expression in innate antiviral response.